Isolation, structure elucidation and antioxidant potential of the major phenolic and flavonoid compounds in brined olive drupes - Owen, Robert; Haubner, R; Mier, Walter; Giacosa, A; Hull, William Edmund; Spiegelhalder, Bertold; Bartsch, Helmut (Food and chemical toxicology, 2003)
Because olives represent an important component of the Mediterranean diet, it is necessary to establish unequivocal identification and quantitation of the major potential antioxidant phenolic compounds they contain. The major phenolic antioxidants in two types of brined olives were isolated and purified by semi-preparative high performance liquid chromatography. Structural analysis was conducted using UV spectrophotometry, mass spectrometry and nuclear magnetic resonance spectroscopy. In particular, completely assigned 1H and 13C NMR data are presented and errors in literature data are corrected. The data show that tyrosol, hydroxytyrosol, 3-(3, 4-dihydroxyphenyl) propanoic acid (dihydrocaffeic acid), dihydro-p-coumaric acid (phloretic acid), the phenylpropanoid glucosides acteoside (verbascoside) and isoacteoside, along with the flavonoids luteolin and apigenin are major components of the phenolic fraction of brined black olives. Brined green olives contain only hydroxytyrosol and traces of other minor phenolics. Brined olives contain even higher concentrations of phenolic antioxidants than olive oil and may, therefore, be more important modulators of cancer chemopreventive activity.